2018
DOI: 10.1155/2018/7202806
|View full text |Cite
|
Sign up to set email alerts
|

BAVP: Blockchain-Based Access Verification Protocol in LEO Constellation Using IBE Keys

Abstract: LEO constellation has received intensive research attention in the field of satellite communication. The existing centralized authentication protocols traditionally used for MEO/GEO satellite networks cannot accommodate LEO satellites with frequent user connection switching. This paper proposes a fast and efficient access verification protocol named BAVP by combining identitybased encryption and blockchain technology. Two different key management schemes with IBE and blockchain, respectively, are investigated,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…These findings broadly support the work in 27 regarding the use of blockchain to verify satellite access. Although the results are in line with those in 27 , PoST has some advantages that make it better than the blockchain-based access verification protocol (BAVP) proposed in 27 :…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings broadly support the work in 27 regarding the use of blockchain to verify satellite access. Although the results are in line with those in 27 , PoST has some advantages that make it better than the blockchain-based access verification protocol (BAVP) proposed in 27 :…”
Section: Discussionsupporting
confidence: 83%
“…Some research efforts discussed the adoption of blockchain to solve various challenges in the space industry and satellite communications. These challenges include the security and privacy of satellite communications 27,28 and satellite data broadcasting 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperledger Fabric [62], FairAccess [92], [93] Accumulator Provides Membership Proofs, Anonymity Batching Techniques for Accumulators in Blockchain [94] Aggregate Signature Fast Signature Verification Tested in Bitcoin [95] Commitment Scheme Non-Repudiation Used in Bullteproof [96] and in Monero [58,65] Decentralised Authorization Data Privacy BlendCAC [97], WAVE [98] Encryption Scheme Confidentiality and Anonymity Kadena [99], Hyperledger Fabric [62], Tendermint [36] Identity Based Encryption No Public Key Distribution Infrastructure BAVP [100], BLIC [101] Incremental Cryptography Efficiency Improvement Kadena [99] Lightweight Cryptography Fast, less Memory/Energy Consumption LSB [102], EVCE [103] Obfuscation Privacy Tested in Bitcoin [104] Oblivious RAM Confidentiality and Integrity Solidus [105], EVORAM [106] Oblivious Transfer Data Privacy Searchain [107], [108] Post-Quantum Cryptography Quantum Resistant Post-Quantum Blockchain [109], [110], [111] Private Information Retrieval Data Privacy Private Blockchain Queries from PIR [86] Proof of Retrievability Cloud Data Recovery Permacoin [112], Retricoin [113], Storj [114] Secret Sharing Data privacy SHARVOT [115], Wanchain [116] Secure Multiparty Computation Privacy of Peers and Smart Contract Enigma [117], Hawk [118], Wanchain [116] Signature Scheme Integrity and Authentication In Every Blockchain e.g. Multichain [64], CryptoNote…”
Section: Access Control Data Privacymentioning
confidence: 99%
“…We identified that the use of IBE within blockchain has started in [100] as well as in supply chain management [101].. Still, there are a lot of challenges and opportunities for other blockchain applications and services.…”
Section: Identity-based Encryption (Ibe)mentioning
confidence: 99%